Assessing the diagnostic value of qPCR for Trichuris trichiura: sub-analysis of a multi-country clinical trial to determine the efficacy of albendazole compared to an albendazole-ivermectin fixed dose combination - Fleitas, Pedro E.; Bengtson, Michel; Messa, Augusto; Bartilol, Brian; Gelaye, Woyneshet; Kepha, Stella; Gandasegui, Javier; de Jesus, Áuria; Novela, Valdemiro; Mandomando, Inácio; Mwandawiro, Charles; Enbiale, Wendemagegn; et al. (Frontiers in Parasitology, 2025)
Trichuris trichiura remains a major global public health concern, particularly in low-resource settings where standard anthelmintic regimens are limited. This study evaluated the diagnostic performance of real-time PCR (qPCR) compared to the Kato-Katz (KK) method in assessing the efficacy of a fixed-dose combination (FDC) of albendazole and ivermectin versus albendazole for the treatment of T. trichiura. The study was embedded within the ALIVE clinical trial (NCT05124691), a phase 2/3 trial conducted in Kenya, Mozambique, and Ethiopia. Stool samples were collected at baseline and 21 ± 7 days post-treatment, with KK performed on fresh samples and qPCR on ethanol-preserved aliquots. In total 534 participants were selected based on positive KK and qPCR at baseline and complete data post-treatment. The primary endpoint was cure rate (CR) by KK and qPCR; secondary endpoints included egg reduction rate (ERR) and cycle threshold (Ct) value incrementation rate (CtIR). Additionally, machine learning algorithms were used to predict infection intensity from qPCR Ct-values and demographic variables. qPCR confirmed the superior efficacy of FDC compared to albendazole as previously shown by KK, but discrepancies were observed in CRs between qPCR and KK, particularly lower qPCR CRs for FDC×1 and FDC×3. Concordance between stool egg counts and Ct-value decreased post-treatment, likely due to reduced KK sensitivity in low-intensity infections. ERR and CtIR showed parallel patterns of efficacy across treatment arms. Machine learning models showed good performance for predicting baseline infection intensity. While not interchangeable, qPCR complements KK and enhances the precision of drug efficacy evaluation in helminth clinical trials.